HUBUNGAN LUARAN SUBJECTIVE GLOBAL ASSESSMENT (SGA) DENGAN DERAJAT KEPARAHAN STROKE - Lisda Amalia; Fadila Arsanti; Ginna Megawati (NEURONA, 2019)
ASSOCIATION BETWEEN SUBJECTIVE GLOBAL ASSESSMENT (SGA) OUTCOMES AND STROKE SEVERITYABSTRACTIntroduction: Stroke is a cerebrovascular disease caused by the sudden death of brain cells. Nutrition plays an important role in stroke. Inadequate intake of nutrients affects severity of stroke. Subjective Global Assessment (SGA) can be used to assess the nutritional status of stroke patients, while severity of stroke is known by assessing neurological deficits based on the National Institute of Health Stroke Scale (NIHSS).Aims: To determine the association between SGA outcomes and stroke severity based on NIHSS.Methods: A cross-sectional study with consecutive sampling in stroke patients who were treated in the neurological ward of Dr. Hasan Sadikin Hospital, Bandung between August-October 2018. Subjective Global Assessment and NIHSS were assessed. Alternative statistical test Fisher’s exact test was used to see the relationship between these two variables.Results: Among 40 patients, 57.5% were female, 37.5% had a stroke at the age of 50-59 years, the main risk factor of stroke was hypertension. Recurrence stroke were more common (52.5%), with most of them were ischemic stroke (60%). The most common neurological deficit was hemiplegia. Subjects with malnutrition (SGA C) were 40%. Fifty percent patients had moderate neurological deficits based on NIHSS. The association between variables by Fisher’s exact test was 0.008.Discussion: There was a significant association between SGA outcomes and stroke severity based on NIHSS.Keywords: NIHSS, nutritional status, SGA, stroke severityABSTRAKPendahuluan: Stroke merupakan penyakit serebrovaskular yang disebabkan adanya kematian mendadak sel otak. Nutrisi berperan penting pada stroke. Asupan nutrisi yang tidak adekuat berpengaruh terhadap derajat keparahan stroke. Subjective Global Assessment (SGA) dapat menilai status gizi pasien stroke, sedangkan derajat keparahan stroke diketahui dengan menilai defisit neurologis berdasarkan National Institute of Health Stroke Scale (NIHSS).Tujuan: Mengetahui hubungan antara luaran SGA dengan derajat keparahan stroke berdasarkan NIHSS.Metode: Analisis potong lintang dengan consecutive sampling pada pasien stroke yang dirawat di bangsal Neurologi RSUP Dr. Hasan Sadikin, Bandung bulan Agustus-Oktober tahun 2018. Variabel yang dinilai pada penelitian adalah SGA dan NIHSS. Uji alternative Fisher’s exact test digunakan untuk melihat hubungan antar variabel.Hasil: Dari 40 subjek penelitian sebanyak 57,5% berjenis kelamin perempuan, 37,5% mengalami stroke pada usia50–59 tahun, memiliki faktor risiko utama hipertensi. Stroke berulang lebih banyak terjadi (52,5%), jenis stroke terbanyak adalah iskemik (60%). Defisit neurologis terbanyak yaitu hemiplegia. Subjek dengan gizi buruk (SGA C) sebanyak 40%. Derajat keparahan NIHSS dengan defisit neurologis sedang yaitu 50%. Hubungan antar kedua variabel, uji alternative Fisher’s exact test memperoleh hasil 0,008.Diskusi: Terdapat hubungan yang bermakna antara luaran SGA dengan derajat keparahan stroke berdasarkan NIHSS.Kata kunci: Derajat keparahan stroke, NIHSS, SGA, status gizi